1989
DOI: 10.1007/bf00315973
|View full text |Cite
|
Sign up to set email alerts
|

Galanin and vasoactive intestinal polypeptide are colocalised with classical pituitary hormones and show plasticity of expression

Abstract: The identity of galanin- and vasoactive intestinal polypeptide-(VIP) immunoreactive (IR) cells in the rat anterior pituitary was investigated using immunocytochemistry and, since levels of both peptides are stimulated by oestrogen, the effect of oestrogen treatment and gonadectomy on the expression of both peptides was examined. In normal male rats, few galanin-IR and very few VIP-IR cells were found. Colocalisation studies performed on 2-microns serial paraffin sections revealed that in these animals galanin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 44 publications
4
54
0
Order By: Relevance
“…Apelin is not the only "hypothalamic" peptide that colocalizes with both hormones. Three other peptides have also been detected within ACTH-and GH-containing cells, such as galanin (6,37), neuromedin U (6), and leptin (41). Interestingly, these peptides are involved in the regulation of food intake (13,17,28), and adipocyte apelin mRNA expression was recently reported to be increased in various mouse models of obesity associated with hyperinsulinemia (2).…”
Section: Discussionmentioning
confidence: 99%
“…Apelin is not the only "hypothalamic" peptide that colocalizes with both hormones. Three other peptides have also been detected within ACTH-and GH-containing cells, such as galanin (6,37), neuromedin U (6), and leptin (41). Interestingly, these peptides are involved in the regulation of food intake (13,17,28), and adipocyte apelin mRNA expression was recently reported to be increased in various mouse models of obesity associated with hyperinsulinemia (2).…”
Section: Discussionmentioning
confidence: 99%
“…The differences among the monkey, human and rat in GAL-immunoreactive localization may indicate that the regulation of GAL in the three species differs. Recently, GAL-LI was observed in the anterior lobe of the pituitary of rats and humans by means of immunohistochemistry [14][15][16][17]. Moreover, GAL mRNA within the anterior lobe of rats has been demonstrated by in situ hybridization [15,16,18].…”
mentioning
confidence: 99%
“…In Dwarf mice, where there is failure of acidophilic proliferation, galanin is also lacking (Hyde et al 1993). We and others have previously demonstrated that galanin is dramatically up-regulated by oestrogens in the anterior pituitary (Kaplan et al 1988, Vrontakis et al 1989, primarily within the lactotrophs of both sexes (Steel et al 1989, Hyde et al 1991, suggesting that the peptide can be present in the same cell type in males and females, depending on the status of oestrogen levels. During pituitary hyperplasia, induced by oestrogen, a correlation exists between the development of pituitary hyperplasia and the increase in galanin mRNA (messenger ribonucleic acid) and peptide concentration (Vrontakis et al 1987, Kaplan et al 1988, Hsu et al 1990.…”
Section: Introductionmentioning
confidence: 84%
“…Immunohistochemical studies indicate that in normal female rats, galanin is detected mainly in lactotrophs, and to a lesser extent in somatotrophs and thyrotrophs (Steel et al 1989, Hyde et al 1991. In the male rat, on the other hand, galanin expression has been confirmed in somatotrophs and, in some studies, thyrotrophs (Steel et al 1989, Moore et al 1999. In Dwarf mice, where there is failure of acidophilic proliferation, galanin is also lacking (Hyde et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation